PENGARUH LIKUIDITAS DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Haryadi, Soni; Ghaniiy Al Hamiid; Heki Marzadi (Universitas Muhammadiyah Bengkulu, 2025)
This research aims to obtain, analyze, and explain the influence of liquidity and capital structure on the value of companies in the Food and Beverage Manufacturing sector listed on the Indonesia Stock Exchange for the years 2021-2023. This research falls into the category of quantitative research. The population of this research is Food and Beverage Manufacturing Companies listed on the Indonesia Stock Exchange in 2021-2023. With the sampling technique used being purposive sampling. The sample used consists of 99 Food and Beverage Manufacturing Sector Companies listed on the Indonesia Stock Exchange. Based on the results of simultaneous testing, the Liquidity variable has an influence on the Company Value, while the Capital Structure variable does not have an influence on the Company Value. A low sigma coefficient for Liquidity indicates that this variable has a more stable and possibly significant influence on the Value of the Company. Keywords: Liquidity, Capital Structure, Company Value